Structural elucidation of GDSL esterase of Photobacterium sp. J15 - Syed Mazlan, Sharifah Nur Hidayah (2017)
GDSL esterase is a member of Family II of lipolytic enzyme that catalyses the synthesis and hydrolysis of ester. The enzyme was further classified in subgroup SGNH hydrolases due to the presence of highly conserved motif, Ser-Gly-Asn-His in four conserved blocks I, II, III, and V, respectively. The broad substrate specificity and regiospecificy make these enzymes as attractive candidates for various applications. To date, the number of structure of GDSL motif enzymes deposited in the Protein Data Bank (PDB) is less than 50 and none of them came from Photobacterium. Besides, the low amino acid sequence identity of only 23% with a passenger domain of autotransporter EstA of Pseudomonas aeruginosa makes this enzyme to be more interesting to be studied structurally. Hence, in order to solve the structure of GDSL esterase (EstJ15), X-ray crystallography was conducted. The recombinant E. coli Rosetta-gami (DE3) pLysS (pET::EstJ15) was overexpressed at 20°C using 0.1 mM IPTG. The crude protein was then undergo two-step chromatography which were affinity chromatography and ion exchange chromatography to produce a highly purified EstJ15 with the tags were cleaved using thrombin. Crystallisation of the purified EstJ15 was carried out via sitting drop vapor diffusion method using 5 mg/ml protein incubated at 15°C. Crystal optimisation of EsJ15 was conducted in order to improve the crystal quality by using different concentrations of salt (ammonium sulphate) and precipitant (PEG 8000). Crystal of EstJ15 was obtained from optimised formulation containing 0.10 M ammonium sulphate, 0.15 M sodium cacodylate trihydrate pH 6.5, and 20% PEG 8000 with crystal dimension of 0.6 mm x 0.2 mm x 0.3 mm. The phase problem was initially solved by using single-wavelength anomalous dispersion (SAD) method using iodide ions as the anomalous scatterer. The crystal was diffracted at 1.78 Å using an in-house X-ray beam and the crystal belongs to primitive orthorhombic space group P212121, with unit cell parameter of a = 49.43, b = 66.28, c = 105.46 Å, α = β = γ = 90°. There is one molecule per asymmetric unit with solvent content of 47.33%. Four iodide ions were located in the structure. The model was then used to solve the native EstJ15 data with higher resolution of 1.38 Å via molecular replacement method. The crystal also belong to primitive orthrombic space group P212121, with unit cell parameter of a = 49.18, b = 66.46, c = 105.47 Å, α = β = γ = 90°. The solvent content is 47.23% with one molecule per asymmetric unit. The crystal structure of Est15 was refined and the final model was evaluated using Ramachandran plot, Verify3D and Errat. The Ramachandran plot evaluation showed that 89.9% of the residues in the crystal structure of EstJ15 are in the most favoured region. Evaluations of the crystal structures by using Errat and Verify3D also showed that the EstJ15 model gave values that were in acceptable range of good structures. The final Rfactor obtained was 0.1580 with Rfree value of 0.1810. The 3D structure of EstJ15 revealed topological organisation of α/β-hydrolase fold of 38.7% helix, 21.3% sheet, 11.0% turn and 29.0% coil. There is one phosphate ion and one chloride ion in the structure. Based on the structural alignment of EstJ15 with other structurally known GDSL motif enzymes, Ser12, Asp302 and His305 were assigned as the catalytic triad with the nucleophile, Ser12 is located near to the Nterminus. Besides, EstJ15 is also grouped under the subgroup of SGNH family with the presence of four conserved blocks I, II, III, and V composed of Ser12, Gly105, Asn161 and His305, respectively. The active site of EstJ15 is located at the centre of the structure, formed a narrow tunnel, channelling to the core. The active site residues including the catalytic triad have low Bfactors of less than 10 Å2 contributed to the high stability of the enzyme that can withstand harsh conditions better. This explain the high salt tolerance of EstJ15 at which the enzyme remained stable and functional in the presence of high salt concentration besides remain stable in various buffers. Besides, the high specificity of EstJ15 toward short chain length substrates (up to C4) was successfully unveiled via protein-ligand docking analysis. The structure elucidation of EstJ15 also provide insights on its catalytic mechanism. In conclusion, the solved structure of EstJ15 revealed exclusive features as compared to other available structure of GDSL motif enzymes. The structure was the first GDSL motif enzyme deposited from Photobacterium and highly valuable due to its tolerance to harsh conditions. Besides, the structure may contribute hugely in the field of structural biology where it may serve as a template in solving the phase problem of proteins with decent amino acid sequence identity to it via molecular replacement, where they are remain unsolvable due to low identity to the current available protein structures.